Hunting affects dry season habitat selection by several bovid species in northern Benin. - DJAGOUN, CHABI A.M.S.; KASSA, B; Djossa, B; COULSON, Tim; MENSAH, GUY APOLLINAIRE; SINSIN, Brice A. (My University, 2014)
Multiple land uses including tourism, hunting, and agriculture around protected areas can be a serious complication for wildlife management. We calculated habitat selection indices (Manly’s alpha) for 10 bovid species in the Pendjari Biosphere Reserve in Benin, west Africa, to assess if habitat use diﬀered in each bovid species between hunting and non-hunting zones. Presence/absence data was used in resource-selection functions based on a generalized linear mixed eﬀect model to examine factors that explained bovid species distribution. We observed stronger avoidance of open habitat types in the hunting zone than in the non hunting zone for the hartebeest Alcelaphus buselaphus, oribi Ourebia ourebi, roan Hippotragus equines, kob Kobus kob, waterbuck Kobus ellipsiprymnus defassa and reedbuck Redunca redunca. In contrast, in grey duiker Sylvicapra grimmia, red-ﬂanked duiker Cephalophus ruﬁlatus, bushbuck Tragelaphus scriptus and buﬀalo Syncerus caﬀer we found no diﬀerences in habitat use between hunted and non-hunted areas. This may indicate that the latter species show more pronounced ecological and behavioural plasticity. Further, resource selection of bovid species on a small scale was inﬂuenced by other factors such as habitat structure, landscape characteristics, and human disturbance. This preliminary assessment of bovid habitat relationships in west Africa suggests that human hunting activities may cause species to alter their habitat selection. We therefore suggest habitat models may need to incorporate this source of variation if they are to accurately predict habitat use or distribution of a species.
Keywords: Hunting zone; ungulates; habitat use; pendjari